A Study of Green Factory Practices in Malaysia Manufacturing Industry - Md Fauzi Ahmad; Siti Norziah Ismail; Mohd Fahrul Hassan; Chan Shiau Wei; Norhadilah Abdul Hamid; Ahmad Nur Aizat Ahmad; Mohd Nasrun Mohd Nawi; Nor Aida Abdul Rahman (International Journal of Supply Chain Management, 2019)
Green Factory is a management tool for eliminate environment burden such as waste, chemical and pollution. Economic development grew too fast has effected major impact to environment. Carbon dioxide, loss of biodiversity, degradation of natural resources, global warming, ozone layer depletion and deforestation have effected on the environment. Based on world statistics, Malaysia has produced 29 million tonnes carbon dioxide and ranked 26th (0.66%) of the 215 countries in the world. 110 world leaders including Malaysia has agreed to work for reducing carbon dioxide gas in the Copenhagen Climate Change Summit 2009. Five main criteria for Green Factory have been identified; (1) Solar power generation systems, (2) Fuel cells system, (3) Cogeneration systems, (4) Air conditioning units and (5) Recycling system. A study was conducted to manufacturing companies that adopted Green Factory practices to assess its their green practices for minimizing environmental problems. The samples were 300 companies in Malaysia. Finally, 20% response rate has been received, with 60 respondents. Based on descriptive result, recycling shows the highest level of practices, followed by solar power cogenerations system, air conditioning units and fuel cells system. This study result shows Green Factory has significant relationship with environment performance (r=0.684, P